Lixo de formigas cortadeiras e seu papel no desenvolvimento de plantas - Santos, Rafaella Santana (2016)
The nest refuse of leaf-cutting ants is the depleted material resulted from the degradation of vegetation harvested, after being partially consumed by workers, along with dead ants and remnants of own symbiotic fungus. It is an extremely rich material in many nutrients (N, P, K, Ca, Mg, S) and may act as an important component of the organic matter in tropical soils, influencing the development and diversity of plant species. In addition, as a renewable material, of relatively easy availability and sampling, it may be a compound with a high potential for organic farming. In this study, we evaluated the influence of nest refuse in two distinct situations: i) as a substrate for the production of vegetables and ii) the plant regeneration of newly deforested plots. To this purpose, the experiments were divided into two stages: first, the nest refuse was evaluated as a component in a substrate for production of lettuce seedlings (Lactuca sativa) and arugula (Eruca sativa) at different concentrations. The experimental design was completely randomized, consisting of six treatments and four replications. The treatments were the following mixtures: Control (Cont) considered the basic substrate containing bark of Pinus sp. + sand + vermiculite (3:3:1 v/v); commercial substrate (Tropstrato®- Trop); nest refuse of two species (Atta opaciceps and Acromyrmex balzani) + basic substrate, in two concentrations: 15% and 25% for each of the species tested (AT15, AT25, AC15 and AC25), respectively. All substrates were subjected to chemical analysis for determination of macro- and micronutrients. The influence of the substrate in the development of seedlings was evaluated by height, root length, stem diameter, dry weight and number of leaves at four periods: 15, 20, 25 and 30 days after sowing. For the second stage of the experiment, a portion of 10 m x 5 m was installed in a regeneration area. The plot was divided into 50 sub-plots of 1 m2, of these, 30 subplots were randomly selected for cataloguing herbaceous species present. After that, the original vegetation was completely removed in the whole plot area. Thereafter, it was installed at the center of each subplot a quadrant of 30 cm x 30 cm, 15 of them containing a mixture of a liter of sieved soil with 250 mL of nest refuse of Atta opaciceps (25% of nest refuse) and the remaining quadrants with 1 liter of bare soil (control). The quadrants remained in the field for 150 days to be reforested. Afterwards, richness, abundance, composition and dry biomass of the herbaceous species that colonized the plots were evaluated. Our results showed that the seedlings of vegetables in treatments containing nest refuse of leaf-cutting ants developed as well as those grown in the commercial product taking into account the evaluated attributes. Possibly, the highest average growth rates of seedlings from the AT25 and AC25 treatments are due to higher nutrient concentrations present in the material. The nest refuse also influenced the development of herbaceous species, since plots receiving nest refuse had higher biomass (vigor) in comparison with the control group. However, there was no influence of nest refuse in species diversity between treatments. Our results suggest that nest refuse produced by leaf-cutting ants may have applicability to either production of vegetables or to be disposed in areas that suffered some disturbance, pointing out another ecological service provided by ants.